A brief literature review retraining amygdala to substitute its irrational conditioned fear and anxiety responses with new learning experiences - Nordin, Simbak; Khairi, Che Mat; Rohayah, Husain; Vidya, Bhagat (2020)
Exposure therapy in the intervention of anxiety treatment and management of anxiety disorders proved to be the most effective. This therapy exposes persons with an anxiety disorder to fear and anxiety-provoking situations, whereby they gain new experiences, which reduces their fear and anxiety. Generally, the amygdala a part of the brain responsible for conditioned fear and anxiety responses such as flee responses, here the new experience and exposure can retrain the amygdala to respond fight rather than flee. The purpose of the article is to promote awareness regarding exposure therapy used in the behavioural interventions of anxiety disorder signifies its role in retraining the amygdala, to be free from conditioned fear. This literature review was completed using electronic databases, an Ovid Medline and PsycINFO search. The current study analysis reviewed 40 full-text articles from the year 1993 to 2015. The search was conducted using keywords such as exposure therapy, amygdala, and anxiety disorders. This article bases on brain behaviour in flight and fight responses. In a nutshell, the article indicates that providing new experiences to the amygdala can bring new responses to fear and anxiety situations.